The peculiarities of conscript’s experienced stress and coping - Autukaitė, Milda; Autukaitė, Gintautas ValickasMilda; Valickas, Gintautas (Psichologija, 2004)
Stress and particularly coping is one of the most widely studied topics in military psychology. That is caused by two main reasons: 1. Military operational environment can be described as extremely stressful. One of the criteria of good military preparedness is the ability to perform in the stressful situations. 2. The price of stress effects on military performance can be very high. This article investigates peculiarities of conscript’s experienced stress and coping according transactional stress model of R. S. Lazarus. Sample of 114 conscripts was participating in the main research. Two scales – „The Primary Appraisal of Military Service Scale“ and „The Conscript’s Experienced Stress Scale“ – were specially constructed for this study. The secondary appraisal of military service was measured with four items proposed by R. S. Lazarus. Coping was assessed by D. Roger „Coping Style Questionnaire“ which was modified by A. Elklit. V. Domanskaitė-Gota and D. Gailienė (Vilnius University) prepared the Lithuanian versijon of this „Coping Style Questionnaire.“ Military service performance was assessed using the evaluation of theoretical tests and general evaluation of physical test. Gathered data confirmed 6 sources of conscripts’ stress. These are: 1) performance of military tasks; 2) tiredness and lack of time; 3) leaders’ behaviour; 4) everyday routine and conflicts; 5) making great demands of conscripts; 6) difficult tasks. It appeared that the biggest stress is caused by everyday minor events (tiredness and lack of time, everyday routine and conflicts), the smallest level of stress is associated with leaders’ behaviour and making great demands of conscripts. The stress level in the beginning of military service can be used for the anticipation of the stress level in the end of military service and also of the experienced stress in military service. Primary appraisal of different military service aspects was strongly related to experienced stress (p ≤ 0.01). Experienced stress was also significantly related to emotional and avoiding coping strategies (p ≤ 0.01). The significant correlation was also obtained while analysing results of military service performance and emotional coping strategy – those conscripts, who use emotional coping strategy more frequently, are worse evaluated for military service performance (p ≤ 0.05). The experienced stress was related to military service performance – those who had experienced small stress were evaluated better for military performance comparing with those conscripts who had experienced big stress.